Long-Term Spinal Ventral Root Reimplantation, but not Bone Marrow Mononuclear Cell Treatment, Positively Influences Ultrastructural Synapse Recovery and Motor Axonal Regrowth - Barbizan, Roberta; Castro, Mateus V.; Ferreira, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; Oliveira, Alexandre L. R. (Mdpi Ag, 2014)
We recently proposed a new surgical approach to treat ventral root avulsion, resulting in motoneuron protection. The present work combined such a surgical approach with bone marrow mononuclear cells (MC) therapy. Therefore, MC were added to the site of reimplantation. Female Lewis rats (seven weeks old) were subjected to unilateral ventral root avulsion (VRA) at L4, L5 and L6 levels and divided into the following groups (n = 5 for each group): Avulsion, sealant reimplanted roots and sealant reimplanted roots plus MC. After four weeks and 12 weeks post-surgery, the lumbar intumescences were processed by transmission electron microscopy, to analyze synaptic inputs to the repaired a motoneurons. Also, the ipsi and contralateral sciatic nerves were processed for axon counting and morphometry. The ultrastructural results indicated a significant preservation of inhibitory pre-synaptic boutons in the groups repaired with sealant alone and associated with MC therapy. Moreover, the average number of axons was higher in treated groups when compared to avulsion only. Complementary to the fiber counting, the morphometric analysis of axonal diameter and "g" ratio demonstrated that root reimplantation improved the motor component recovery. In conclusion, the data herein demonstrate that root reimplantation at the lesion site may be considered a therapeutic approach, following proximal lesions in the interface of central nervous system (CNS) and peripheral nervous system (PNS), and that MC therapy does not further improve the regenerative recovery, up to 12 weeks post lesion.
Keywords: ventral root avulsion; fibrin sealant; root reimplantation; mononuclear cells; ultrastructure